Risk and Guideline for Risk Management on Budget of School in Phitsanulok Primary Education Service Area Office 3 - Sunphum, Nikorn; Wannasri, Jitima (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2018)
An aim of this study was to identify risk which occurred in budget management and approach on budget of school in Phitsanulok Primary Education Service Area Office 3 .The study was divided into 2 steps. Firstly, risk education on budget of school in Phitsanulok Primary Education Service Area Office 3. The samples were 313 people who were directors and the finance teachers in Phitsanulok Primary Education Service Area Office 3 by purposive sampling. Data were collected by using a 5 rating-scale questionnaire and analyzed by using mean and standard deviation. Secondly, the risk management approach on budget of school in Phitsanulok Primary Education Service Area Office 3 by using semi-structured interview of 5 people. The content analysis was a tool used for data analysis in the second step. The results found that the risk management approach on budget of school in Phitsanulok Primary Education Service Area Office 3 was at a low level. The first top 3 aspects related to the risks which have occurred in managing and developing schools were as follows: 1) the finance teachers lacked the understanding of operation according to budget regulations. They were mistaken on disbursement off budget withdrawal near the end of the fiscal year. They did not do the summary of budget spending report. The solutions were as follows: training and workshop should be held every year, and channel of learning by website should be created within the area. The directors should reiterate the disbursement every three month and annual report should be completely and strictly made. 2) In terms of account management, the finance teachers had more teaching load and lacked understanding on regulation and operation on finance without a clear manual which resulted in the account mistake. The solutions were as follows: organizing the meeting of the finance teachers and revise their task on duty as well as their teaching loads in a balance manner, workshop on understanding and rules, proper operational procedures every year along with providing the manual and online manual via the website in the area. 3) In terms of procurement and property management, the procurement officers lacked understanding on rules of procurement. They did not survey what to purchase for supplies and materials and check them after being delivered. The solutions were as follows: training and workshop on rule and steps for procurement and property management should be organized every year; channels of learning should be added via websites in every education service area office. The survey on supply and material procurement should be conducted before the project implementation. The know-how persons in procurement and checking supply and material should be provided from other units for the consultation.